Tesmin, Metallothionein-Like 5, is Required for Spermatogenesis in Mice. Issue 4 (9th January 2020) - Oji, Asami; Isotani, Ayako; Fujihara, Yoshitaka; Castaneda, Julio M; Oura, Seiya; Ikawa, Masahito
Abstract: In mammals, more than 2000 genes are specifically or abundantly expressed in testis, but gene knockout studies revealed several are not individually essential for male fertility. Tesmin ( Metallothionein-like 5 ; Mtl5 ) was originally reported as a testis-specific transcript that encodes a member of the cysteine-rich motif containing metallothionein family. Later studies showed that Tesmin has two splicing variants and both are specifically expressed in male and female germ cells. Herein, we clarified that the long ( Tesmin-L ) and short ( Tesmin-S ) transcript forms start expressing from spermatogonia and the spermatocyte stage, respectively, in testis. Furthermore, while Tesmin -deficient female mice are fertile, male mice are infertile due to arrested spermatogenesis at the pachytene stage. We were able to rescue the infertility with a Tesmin-L transgene, where we concluded that TESMIN-L is critical for meiotic completion in spermatogenesis and indispensable for male fertility. Abstract : TESMIN protein, a member of metallothionein family, is essential for mouse spermatogenesis, especially in the meiotic stage.